THE IMPORTANCE OF REHABILITATION IN CHILDREN WITH HEART DEFECTS AFTER SURGERY (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
Congenital heart disease is the most common neonatal congenital defect. The variety and severity of clinical manifestations depend on the heart structures and their functional impact [1]. According to analyses, 8-10 out of every 1,000 infants are born with congenital heart defects worldwide. 72% of them require surgery in the first year of life. Through timely surgeries, 97% of these young patients can return to a healthy life [9].